2007
DOI: 10.1177/000313480707300920
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy and Interval Appendectomy for Perforated Appendicitis in Children: A Selective Approach

Abstract: The role of initial nonoperative treatment in pediatric perforated appendicitis remains controversial. We examined our outcomes after using this approach in a selective manner. Children with perforated appendicitis treated during a 28-month period were retrospectively reviewed. Antibiotics and delayed appendectomy were used if there were more than 3 days of symptoms, absence of bowel obstruction, absence of diffuse peritonitis, and an appendiceal mass. Of 221 patients with perforated appendicitis, 32 (14%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…The second-line antibiotics did not increase postoperative complications (p ¼ 0.99) or recurrence (p ¼ 0.99). These data are consistent with a previous report that failure of medical treatment did not increase morbidity 7 and discordant with another. 8 In our experience, nonoperative management of appendiceal mass and abscess decreased the rate of postoperative intra-abdominal abscess from 18 to 3% (2/64) and we recommend it.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The second-line antibiotics did not increase postoperative complications (p ¼ 0.99) or recurrence (p ¼ 0.99). These data are consistent with a previous report that failure of medical treatment did not increase morbidity 7 and discordant with another. 8 In our experience, nonoperative management of appendiceal mass and abscess decreased the rate of postoperative intra-abdominal abscess from 18 to 3% (2/64) and we recommend it.…”
Section: Discussionsupporting
confidence: 92%
“…As a result of this protocol, the nonoperative management was achieved in 94% of children which is one of the highest success rates reported. [7][8][9]13,17 Despite this second-line antibiotics, the mean lengths of hospitalization and antibiotherapy were not increased and seem acceptable to us. The mean length of stay after ILA was 1 day (range, 1-8 days) and in 16 cases (25%) the surgeon did not notice any residual inflammation inside abdominal cavity.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…132,134 Recent evidence has shown that acute appendicitis can be treated successfully nonoperatively in adults and children. 58,[140][141][142] Two meta-analyses have demonstrated that conservative treatment with antibiotics only is associated with a lower risk of complications without differences in length of hospitalization. 68,143 However, the success of initial nonoperative treatment of complicated appendicitis has stimulated some surgeons to question the need for subsequent interval appendectomy.…”
Section: Laparoscopic Appendectomymentioning
confidence: 99%